-2(z+4)=44

Simple and best practice solution for -2(z+4)=44 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(z+4)=44 equation:


Simplifying
-2(z + 4) = 44

Reorder the terms:
-2(4 + z) = 44
(4 * -2 + z * -2) = 44
(-8 + -2z) = 44

Solving
-8 + -2z = 44

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + -2z = 44 + 8

Combine like terms: -8 + 8 = 0
0 + -2z = 44 + 8
-2z = 44 + 8

Combine like terms: 44 + 8 = 52
-2z = 52

Divide each side by '-2'.
z = -26

Simplifying
z = -26

See similar equations:

| (u-6)*10=100whatisu | | -4q-8=16 | | 5x^8+35x^7+60x^6= | | 10t-20=60 | | (8a-7b)=16a^2b-14ab^2 | | 10+-20=60 | | N-41=20+4 | | -4(c+1)+2c=3(2b-1) | | 4(4y+5)=60+5(y+3) | | x^5-x^4-5x^3-x^2+8x-4=0 | | 4(-5y+1)=-96 | | k.1/3=5 | | 6+8n+2+8n+2= | | 3N+5=40+25 | | X^2-5x+6=6x-18 | | 12b-5-2b=2 | | A(x+2)+B(x-1)-1=0 | | 3x-4+5=x | | 1.5=2/1.7 | | n^3-6*n^2+5*n-324=0 | | 4x+2=3-(5x-6) | | 2m^2-7m=12 | | 3x-4-5=x | | 7(x+1)=-14 | | 17-4x=13+x | | -7xb=b-49 | | X-.75X=25 | | x+2+7x=-16 | | x=(y+4)*log(2y+3) | | 3x^2-8x+3y^2+4=0 | | 216z^3-125y^3= | | B/19-7b/19=54/19 |

Equations solver categories